Estudio de la cinética de la interacción de diferentes especies de fusarium spp., asociados a la marchitez vascular del babaco Vasconcellea heilbornii var. pentágona - Medina Salinas, Luis David (2015)
In recent years Babaco production has decreased significantly by 75%, due to the presence of a disease known as "Vascular wilt Babaco (MVB)", caused by the fungus Fusarium oxysporum. This disease has spread rapidly throughout the Ecuadorian territory, bringing losses of 100% in production, 50% both in growing plants and 50% in production plants. Against this phytosanitary problem, many farmers chose not to continue cultivating this fruit, due to ignorance of the causative agent and the absence of control measures to mitigate the disease. This research aims to evaluate the kinetic and interaction of different species of Fusarium., Using fungal isolates of Fusarium, which causes vascular wilt in Babaco (Vasconcellea heilbornii Var. Pentagonal), under greenhouse conditions. An experimental design was completely randomized with five treatments (T1, T2, T3, T4 and T5) and nine aftershocks, resulting inoculation 6 fungal isolates. 150 seedlings Babaco three months old, grown in sterile soil (1: 1 soil, sand and peat 2) were used. The method of inoculation was dip root, for evaluating the pathogenicity evaluation scale proposed by Veintimilla (2000) was used. The results obtained show that T2, T3, T4 and T5 treatments showed typical symptoms of Vascular Wilt Babaco (MVB). Therefore, following Koch's postulates, it was confirmed that all four treatments were able to produce a high degree of disease severity in growing Babaco